The Effectiveness of the Combination of Moringa Seeds and Leaves (Moringa Oleifera) as a Natural Coagulant to Reduce Turbidity in Excavated Well Water in Wumialo Village, Gorontalo City - Melani Koniyo; Irwan; Moh. Rivai Nakoe (Universitas Muhammadiyah Palu, 2026)
Dug well water is still widely used by the community as a source of clean water, but the quality often does not meet turbidity requirements. High turbidity levels can reduce water quality and increase health risks, so effective, safe, and environmentally friendly water treatment efforts are needed by utilizing natural coagulants. The purpose of this study is to determine the effectiveness of the combination of moringa seeds and leaves (Moringa oleifera) as a natural coagulant in reducing the turbidity level of dug well water. The type of experimental research with a pre-test-post test research design uses a combination dose of moringa seeds and leaves, namely 10 mg, 20 mg and 30 mg. The water sampling technique is Purposive sampling. Data analysis used the One-Way Anova test and the LSD (Least Significant Difference) follow-up test. The results of the study showed that the turbidity value of dug well water in pre-test conditions was 15.5 NTU. The reduction in cloudiness after treatment with a dose of 10 mg had an average of 3.77 NTU (75.67%), the 20 mg dose of 2.53 NTU (83.67%), and the 30 mg dose of 3.17 NTU (79.54%). The Anova One-Way test showed a significant difference in effectiveness between doses of coagulants (p-value = 0.038 < 0.05). Follow-up LSD tests showed a significant difference between the 10 mg and 20 mg doses (p-value = 0.014 < 0.05), but there was no significant difference between the 10 mg and 30 mg doses (p-value = 0.146 > 0.05), as well as between the 20 mg and 30 mg doses (p-value = 0.128 > 0.05). It is recommended for subsequent researchers to test variations in stirring speed as well as other water quality parameters.